Investigation Report of A Fatal Case of Dengue Hemorrhagic Fever in Wihan Daeng District, Saraburi Province, May 2018 - Pummanee, Narapat; Pangchak, Thananontorn; Saenaprom, Wanida; Khantee, Sinthara; Trichaisri, Nichapa (Journal of Medical and Public Health Region 4, 2019)
This investigation is to confirm the outbreak of Dengue Hemorrhagic fever in Wiharn Daeng District , Saraburi. This study consist studying of the occurring of the disease ,sources and disease transmission. By studying the illness history of this patient as well as illness history of other patients by definition, including environmental sanitation, index of prevalence of mosquito larvae, laboratory tests and other investigation result. This 68-year-old male had no history of any previous illness ,never had any history of dengue fever. He came back to his home on May 12, 2018 and he start to have fever on May 14, 2018. He did not have any treatment or recieve any medication. On May 16, 2018, he attended Pratye Hospital and the investigation revealed Dengue Ns1 Ag: + ve, Plt 7,000 cells / mm3. The diagnosis was Dengue Shock Syndrome and he was then refered to Maharaj Nakhon Ratchasima Hospital . The history findings there was fever, muscle aches, chills, diarrhea . Investigation findings was Dengue Ag results: + ve, Hct = 31.6%, WBC = 12,000 cells / mm, Plt = 10,000 cells / mm. He died on 19 May 2018 at 00.30. There is no other report about this disease at this time in this area. And from the report 506 revealed the outbreak in the early school age group. The first patients was found on March 4, 2018, and case no. 3, 5-6 and 9-11 were found on 1-26 April 2018, 6 cases were diagnosed at the same period of time. 7 patients were found in the company home in 4 zones B,C,F and G, from the overall 7 zones. There were 1,729 rooms with about 3,192 persons occupied . This patient lived at Zone B15 with the surrounding 22 houses which was a single storey wooden house with no mosquito net ,no bathroom inside the house. There was a shared bathroom. The environment is quite crowded, not being hygienic, there was a lot of debris, damp. The environment was crowed with debris, and there is still water drainage in front of the house, and very bad odour. There are 5 people staying with the patient in this house. There were hanging large bags which is suitable for mosquitoes living. In the surrounding 100 meter the HI values was 2.61, CI = 2.54, BI = 2.61, which was not higher than standard. The source of this dengue hemorrhagic fever outbreak should occurred from local area. The mosquitoes breeding sites could not be eleminated properly to zero as shown by HI = 2.61, CI = 2.54, BI = 2.61. The local people did not realize the importance of mosquito elimination. Both indoor and outdoor environments also contribute to occurring ,transmission and spreading of the disease.